Preparação de nanocompósitos baseados na intercalação de argilominerais em matrizes ureia-formaldeído para aplicação como fertilizantes de liberação controlada - Yamamoto, Cíntia Fumi (2014)
The increase on the price of fertilizers, and the high Brazilian importing dependency of this material, raise the cost of cultures. Such cost may be reduced by more efficient and efficiently used fertilizers. From an economical point of view, urea is one of the most interesting commercial choices available for nitrogen based fertilizers. However, using it in its pure form is not appropriate, for the loss of nitrogen through volatilization into the atmosphere may reach extreme values, diminishing its efficiency when applied on the ground's surface. In this work, nitrogen losses can be reduced by condensation polymerization of urea and formaldehyde, and by adding mineral clay to this nanocomposite to act as a diffusion barrier and to adsorb urea. Extrusion shows to be an advantageous process to produce in one step a bead with satisfactory strength and easy handling. A solid precursor of formaldehyde (paraformaldehyde) was successfully used to facilitate the polymerization process, and the reaction occurred in the bead due to the formation of formaldehyde in situ owing to the temperature rise and water addition. Incubation soil tests showed that the higher content of polymer phase in the material trended to cause a higher delay in the release of total N applied. It was also observed an increase in mechanical strength and Young modulus by flexural bending strength tests to higher content of polymer phase compositions. Although the final bead fertilizer has a lower N content than pure urea, its use is potentially interesting owing to extrusion mass production process and the subsequent polymerization step in moderate temperature.